Determination of Cadmium (Cd) Metal Content in Milkfish at Port of Tanjung Mas - Feni Nilasari; Yari Mukti Wibowo (Biomedika, 2020)
The location of milkfish ponds around the Port of Tanjung Mas is adjacent to an industrial area. This can increase the possibilities of milkfish being contaminated by heavy metals, for example Cadmium (Cd) metal. Therefore it is necessary to determine the levels of Cadmium metal in milkfish that are cultivated in ponds around the Port of Tanjung Mas. The aims of this study is to find out the levels of Cadmium metal in milkfish samples at the Port of Tanjung Mas whether or nor it exceeds the threshold. The method commonly used for metal analysis is the Atomic Absorption Spectrophotometry (AAS) method, because this method is simple, selective and sensitive for analyzing metal content in a sample of animal origin, such as milkfish. In the initial treatment, milkfish samples were separated between meat and bones. The milkfish was then dried by heating at 150oC for 1 hour and continuing with ashes up to 550oC. The ash-shaped sample was dissolved in concentrated HNO3 and diluted with aquabidest. The aqueous sample solution was analyzed using ASS at a wavelength of 228 nm to determine the metal content of Cd in the sample. The level of Cd metal in milkfish samples analyzed using ASS, showed that it was still in accordance with the quality standard, which was below the threshold set in SNI No. 7387: 2009. Samples of milkfish taken from several pond locations showed that the farther pond was from the industrial area, the less Cd metal pollution in milkfish in the pond area.